Variable Thrust Rates of the Eastern Qilianshan Mountain Front, Northeastern Margin of the Tibet Plateau and Its Implication to the Topography of the Yongchangnan Shan - Jinghao, Lei; Youli, Li; Zhikun, Ren; Xiu, Hu; Jianguo, Xiong; Fei, Liu; Jinrui, Liu (Frontiers in Earth Science, 2021)
It is commonly assumed a thrust has a constant slip and uplifting rate along the strike, however, this simplified model cannot always be consistent with field observations. The along strike slip patterns with variable offsets and rates contain plenty of information about the characteristics of the faulting behavior and its relationship with adjacent faults. The east Qilian Shan, located at the northeastern margin of the Tibetan Plateau, provides us an excellent opportunity to study the faulting behavior in a thrust-bounded range area. Besides the previously reported slip rates of the N-W trending tectonics across the region, we augmented the data by surveying the Fengle fault (FF), one of the north bounding thrust of the Yongchangnan Shan. Another north bounding fault is the Kangningqiao Fault (KNF), east of the FF. Based on the vertical offsets and rates along the fault, we constructed the slip pattern along the strike. The results show the vertical slip rate of the FF ranges from 0.7±0.1 mm/a to 2.8±1.3 mm/a across three surveyed sites. The slip rate decreases from the east to the west. The FF and KNF might be interred as two segments of a single segmented thrust controlling the uplift of the Yongchangnan Shan. By comparing the uplift onsets in the study region, we discuss the northward propagated deformation along the northeastern margin of the Tibet plateau.